Recovery from Goodpasture's syndrome after immunosuppressive treatment and plasmapheresis. - Lockwood, C M (1975)
A patient with Goodpasture's syndrome has recovered after treatment with immunosuppressive drugs (cyclophosphamide and prednisolone) and removal of circulating antibodies by plasma exchange. This was performed on seven occasions and seems to have hastened the decline in circulating antibody levels. Undertaken early in the course of the disease plasmapheresis could prove a useful addition to its therapy.